Comparative Study of Pulsed Microwave and Hydrodistillation Extraction of Piperine Oil from Black Pepper - Olalere, Olusegun Abayomi; Nour, A. H.; R. M., Yunus; Alara, Oluwaseun Ruth; Jayshree, Thraisingam (IIUM, 2017)
Black pepper is a tropical crop with an extensive medicinal potential in ethnomedicine and nutraceutical applications. The pungent bioactive piperine is responsible for this functions which efficacy requires an efficient technologies for optimal extraction process. There is therefore a need to determine the best factor settings that optimize the relative efficiency of the system with minimal variability. In this study, the best factor settings was achieved using Taguchi parametric L9-orthogonal methodology. The extraction parameters considered under this study were extraction time, microwave power, particle size and molar ratio. An optimal extraction condition was achieved at 90 min extraction time, 350 W microwave power, 0.105 mm particle size and 10 ml/g molar ratio. The signal-to-noise ratio (SNR) otherwise known as response optimizer is an ideal metric in the determination of this optimum condition. The performance evaluation of reflux microwave extractor in relation to the hydrodistillation system placed the optimal efficiency and signal-to-noise ratio at 155.72% and 43.85, respectively. The higher optimal efficiency obtained indicated that the microwave reflux extraction is better and more efficient than the conventional hydrodistillation techniques.